2022
DOI: 10.3390/jof8060553
|View full text |Cite
|
Sign up to set email alerts
|

UvKmt2-Mediated H3K4 Trimethylation Is Required for Pathogenicity and Stress Response in Ustilaginoidea virens

Abstract: Epigenetic modification is important for cellular functions. Trimethylation of histone H3 lysine 4 (H3K4me3), which associates with transcriptional activation, is one of the important epigenetic modifications. In this study, the biological functions of UvKmt2-mediated H3K4me3 modification were characterized in Ustilaginoidea virens, which is the causal agent of the false smut disease, one of the most destructive diseases in rice. Phenotypic analyses of the ΔUvkmt2 mutant revealed that UvKMT2 is necessary for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In particular, H3K4me3 is widely recognized as a marker of active transcription to a larger degree than H3K4me1/me2 and mainly enriches at the promoter and transcriptional start site ( 55 57 ). In U. virens , ChIP-seq and RNA-seq assays revealed that H3K4me3 participates in transcriptional activation of conidiation-related and pathogenic genes ( 23 ). Similarly, the expression of COMPASS target genes is highly correlated with H3K4me3 at transcription start sites in M. oryzae ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, H3K4me3 is widely recognized as a marker of active transcription to a larger degree than H3K4me1/me2 and mainly enriches at the promoter and transcriptional start site ( 55 57 ). In U. virens , ChIP-seq and RNA-seq assays revealed that H3K4me3 participates in transcriptional activation of conidiation-related and pathogenic genes ( 23 ). Similarly, the expression of COMPASS target genes is highly correlated with H3K4me3 at transcription start sites in M. oryzae ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the importance of Set1-mediated H3K4 methylation has been gradually revealed in fungi. Disruption of Set1 homologs causes a severe reduction in vegetative growth and/or conidiation of several crop fungal pathogens, including Magnaporthe oryzae ( 19 ), Fusarium graminearum ( 20 ), Fusarium fujikuroi ( 21 ), Fusarium verticillioides ( 22 ), Ustilaginoidea virens ( 23 ), and Aspergillus flavus ( 24 ). MoSET1 is involved in infection-related morphogenesis of M. oryzae , such as conidiation and appressorium formation ( 19 ).…”
Section: Introductionmentioning
confidence: 99%